The Fourth Industrial Revolution and Its Implications for Regional Economic Integration in ASEAN. Issue 1 (April 2019) - Menon, Jayant; Fink, Anna
Abstract: This article explores the impact of the Fourth Industrial Revolution (4IR) on the Association of Southeast Asian Nations (ASEAN). It argues that technologies of the 4IR can bring huge benefits such as empowerment for small- and medium-sized enterprises and opportunities for countries to leapfrog traditional pathways of development. It will also bring tremendous challenges such as deep disruption to labour markets and the potential of rising inequality. To address the challenges and seize the opportunities of the 4IR, ASEAN will need a new way of formulating policy and regulation that will require: (a) evolution of the ASEAN Secretariat to become a 'platform organisation', (b) greater delegation of key activities to affiliated functional bodies, (c) a shift from long-term blueprints to three-year rolling plans, (d) democratise and decentralise and (e) establish multi-country test beds. JEL Codes: F14, F15